Tao is hidden and nameless: Exploring the mysticism path of Laozi and Zhuangzi - Sun, Yue (HTS teologiese studies, 2024)
The contemporary interpretation of Lao-Zhuang’s thought reveals a multidimensional dialogue between tradition and modernity, the local and the exotic, and East and West. The interaction between Lao-Zhuang’s thoughts and Western religious philosophy can be explored through the lens of mysticism. By examining the non-material nature of the Tao, the transcendence of language, and the cultivation goal of the unity of nature and humanity, we can discern the relationship between the cultivation practices in Lao-Zhuang’s thought and religious mysticism. The chaos, uncertainty, infinity and nothingness associated with the non-physical Tao present a subtle and mysterious depiction of nature. The silence of the perfect man, who sees things in terms of the Tao, along with their conversion to the Tao, steadfastness to the Tao, flexibility in treating things according to the Tao and freedom to be one with the Tao, provides an ethical realm of inner cultivation. Through the dialogue between Lao-Zhuang’s philosophy and Western religion, we can uncover the commonalities and differences between Chinese and Western cultures, as well as the significant value of Lao-Zhuang’s thought in contemporary cultural and philosophical discussions.Contribution: This article examines the relationship between cultivation practice in Lao-Zhuang’s thought and religious mysticism from the perspective of cross-cultural research. By discussing the immateriality and infinity of ‘Tao,’ as well as the relationship between Tao and name, speech and debate, it presents the mystery of Tao. Through the non-cognitive practice mode of real people, they experience ‘Tao’ and achieve the realm of ‘Harmony between nature and man,’ demonstrating the mystery of cultivation efforts.